STUDENT BUSINESS DEVELOPMENT BASED ON ELECTRONIC CUSTOMER RELATIONSHIP MANAGEMENT - Hastuti, Indra; Sopingi, Sopingi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This research produces a student business development model based on Digital Business management and Electronic Customer Relationship Management. This research is a qualitative case study with an action research approach. Researchers conducted an exploration of program applications, training and application of models to student business activities, starting with mapping student businesses according to their competencies, providing training on the use of Electronic Customer Relationship Management (E-CRM) information technology as a means of managing customers in businesses run by students for retention. customers increase. The results of the study showed that there were 8 types of businesses that were engaged in by students from 30 samples of students who owned businesses. Based on data analysis after students implemented the E-CRM Model development, student business development in terms of number of customers, turnover and profits increased by 20%